A method for preparing high-porosity foamed carbon and the prepared foamed carbon
By using PVDF as a precursor and combining a variety of pore structure control technologies, high porosity carbon foam is prepared, which solves the problems of poor product quality and difficult pore structure control in the preparation process of foam carbon materials in the existing technology, and realizes foam The high porosity and diversified control of carbon have expanded its application fields.
Patent Information
- Application Number
- CN202211637087.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-20
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-12-20
AI Technical Summary
The foam stabilizers and coupling agents used in the preparation process of existing foam carbon materials will affect the carbonization process, resulting in poor product quality. At the same time, the pore structure of the precursor materials is difficult to regulate the wide range, limiting the application of foam carbon.
Using polyvinylidene fluoride (PVDF) as a new carbonaceous precursor, high porosity carbon foam was prepared by integrating thermally induced phase separation, non-solvent induced phase separation, soluble template dissolution method and high temperature pyrolysis to achieve pore Wide range and fine control of structure.
The high pore rate of foam carbon and the diversified regulation of the pore structure. The air pore rate, apparent density, and skeleton density can be adjusted within a certain range. Super capacitors and other fields.
Smart Images

Figure CN115959660B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of porous carbon materials, and in particular relates to a method for preparing high-porosity foamed carbon and the prepared foamed carbon. Background Art
[0002] Carbon foam is a new type of low-density porous carbon material with a three-dimensional network structure. It has a highly developed pore structure and a glassy carbon skeleton. Therefore, it has the dual characteristics of carbon materials and foam materials, such as high catalytic activity, strong adsorption capacity, high chemical stability, easy functionalization of carbon walls, and controllable graphitization and doping of glassy carbon skeletons from carbon materials, as well as thermal shock resistance, easy processing and good physical and chemical properties such as thermal conductivity and wave absorption from foam materials. Due to its excellent comprehensive performance, carbon foam has great development and application potential in many fields such as catalysis, chemical industry, energy storage, stealth, nuclear protection, electrodes, hybrid material synthesis and porous ceramic preparation, which has attracted great attention from scientists and engineers at home and abroad.
[0003] The structure, performance and preparation method of foamed carbon are closely related to the precursor materials used. From the perspective of the precursor raw materials, they are roughly divided into the following categories: organic polymers, mesophase asphalt, coal and biomass. For example, patent CN110921648A discloses a one-step preparation method of a light and high-strength microsphere phenolic resin-based foamed carbon, which uses a water-soluble phenolic resin as a foaming raw material, a mixed solution of anhydrous ethanol and distilled water as a solvent, and a foaming resin solution is prepared together with the foaming raw material, the solvent, a foaming stabilizer and a coupling agent, and then the foaming and curing are performed in a high-temperature autoclave to obtain a phenolic resin-based foam solidified body, and finally the foam solidified body is placed in a carbonization furnace and heated and carbonized with a certain temperature rise program, and a light and high-strength microsphere phenolic resin-based foamed carbon is prepared in one step. Although the invention can achieve a wide range of adjustment of the pore structure of the foamed carbon through process control, the addition of a foaming stabilizer and a coupling agent will affect the subsequent carbonization of the foamed carbon to varying degrees, resulting in poor product quality. Patent CN108455560A discloses a method for preparing low-density foamed carbon, which uses bamboo leaves as carbonaceous precursors to prepare foamed carbon. It can give biomass materials a higher added value and embody the concept of renewable energy. However, due to the pore structure of the precursor itself, it is difficult to achieve a wide range of control over the pore structure of the foamed carbon, which limits the application of the foamed carbon. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing high-porosity foamed carbon and the prepared foamed carbon.
[0005] Polyvinylidene fluoride, PVDF for short, is a non-reactive thermoplastic fluorine-containing polymer with a mature and highly commercialized synthesis process. It has been widely used in the fields of chemical industry, semiconductor, pharmaceutical and national defense industry. In the prior art, the most commonly used methods for synthesizing porous PVDF are thermally induced phase separation and non-solvent induced phase separation, which are the main phase transformation pathways. The pore structure can be finely controlled to meet the needs of different application fields. In addition, PVDF has a residual carbon rate of about 30% after high-temperature pyrolysis. In view of the above characteristics of PVDF, the present invention uses highly commercialized PVDF as a new carbonaceous precursor for synthesizing high-porosity foam carbon. By integrating thermally induced phase separation, non-solvent induced phase separation, soluble template dissolution method and high-temperature pyrolysis, high-porosity foam carbon is prepared, while achieving a wide range and fine regulation of the pore structure of the foam carbon, broadening the derivative products of PVDF and its application fields.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing high-porosity foamed carbon comprises the following steps:
[0008] (1) Mixing: Preheat the organic solvent to 80-120 °C, then add the porogen and mix evenly, and finally add PVDF and stir for 1-3 h to obtain a mixed suspension.
[0009] (2) Degassing: Keep the mixed suspension at 80-120°C for 2-4 hours, and then degasse;
[0010] (3) Curing: Pour the degassed mixed suspension into a mold, and then let it stand at 1-10°C for 15-45 minutes. After the curing, demold the mixture to obtain a cured product.
[0011] (4) Water bath: Soak the solidified body in deionized water at 1-10°C for 24-72 hours;
[0012] (5) Boiling: Soak the solidified body after the water bath in deionized water, then heat it to 80-120°C and boil it for 1-4 hours. After boiling, take it out and dry it at room temperature.
[0013] (6) Pyrolysis: The solidified body after boiling is placed in a tubular atmosphere furnace, first heated to 100-150°C and kept warm for 1-4 h, then heated to 500-1000°C and kept warm for 0.5-2 h, and finally cooled to room temperature to obtain high-porosity foamed carbon.
[0014] As a preferred embodiment of the above technical solution, in step (1), the organic solvent is any one of N-methylpyrrolidone, N,N-dimethylformamide, triethyl phosphate and dimethyl sulfoxide. Preferably, the organic solvent is triethyl phosphate.
[0015] As a preferred embodiment of the above technical solution, in step (1), the mass ratio of the porogen to the organic solvent is 1:(30-50); the mass ratio of the PVDF to the porogen is 1:(0.05-0.30).
[0016] Furthermore, in step (1), the mass ratio of the porogen to the organic solvent is 1:(30-40); the mass ratio of the PVDF to the porogen is 1:(0.10-0.20).
[0017] As a preferred embodiment of the above technical solution, in step (1), the system temperature is always maintained at 80-120°C.
[0018] As a preferred embodiment of the above technical solution, in step (1), the pore-forming agent is one or more of water-soluble starch, glucose, fructose, maltose, raffinose and sodium chloride particles. Preferably, the pore-forming agent is water-soluble starch.
[0019] In the above technical scheme, water-soluble starch is mainly composed of branched starch, and the basic structural unit is α-D-pyranose glucose, with irregular structural arrangement, molecular weight up to several million, poor crystallinity, soluble in cold water, and high viscosity. The present invention selects water-soluble starch as a porogen, mainly because it dissolves slowly at room temperature, but is easily soluble in water and removed after heating, and is cheap, biocompatible, and can be recycled and reused later. The monomer substance of water-soluble starch is a polyhydroxy organic matter that can form hydrogen bonds with PVDF, induce PVDF crystallization through hydrogen bonding, and can form a large-sized pore structure in PVDF after the soluble template is dissolved and removed.
[0020] As a preferred embodiment of the above technical solution, in step (3), the mold is a glass mold that is preheated to 80-120°C.
[0021] As a preferred embodiment of the above technical solution, the water bath in step (4) further comprises: during the soaking period, the deionized water is replaced every 12 to 24 hours.
[0022] As a preferred embodiment of the above technical solution, in step (6), the first heating is carried out in an air atmosphere, and the second heating is carried out in a nitrogen atmosphere; the heating rate of the second heating is 2-20°C / min.
[0023] In the above technical solution, step (3) solidification is to complete preforming and thermally induced phase separation; step (4) water bath is to complete non-solvent phase separation; step (5) water boiling is to dissolve and remove the soluble template in the solidified body.
[0024] The present invention first forms a developed pore structure in PVDF by integrating three typical pore-forming technologies, namely, thermally induced phase separation technology, non-solvent induced phase separation technology, and soluble template dissolution method, which are highly compatible in the process. Then, the PVDF skeleton is transformed into a glassy carbon skeleton through high-temperature pyrolysis technology, and at the same time, the developed pore structure of PVDF is inherited to the foam carbon. Among the three pore-forming technologies, thermally induced phase separation and non-solvent induced phase separation are mainly responsible for the formation of small-sized pores in PVDF, while the soluble template dissolution method is mainly responsible for the formation of large-sized pores in PVDF. The three have different focuses. The high degree of integration of the technologies can not only give the foam carbon a high porosity through PVDF, but also achieve diversified regulation of the pore structure of the foam carbon by adjusting the process parameters of the three technologies.
[0025] Another object of the present invention is to provide a carbon foam.
[0026] A high-porosity foamed carbon is prepared by any of the above methods.
[0027] In summary, the present invention has the following beneficial effects:
[0028] 1. The present invention applies commercial PVDF to the preparation of foamed carbon by rationally designing the foamed carbon preparation process, thereby expanding the use, derivative products and application fields of PVDF.
[0029] 2. The present invention integrates three pore structure control technologies, namely, thermally induced phase separation, non-solvent induced phase separation and soluble starch template dissolution, to achieve not only high porosity of foamed carbon, but also wide-range and fine control of pore structure. The apparent porosity, apparent density and skeleton density of foamed carbon can be 63.70-81.79% and 0.25-0.47 g / cm, respectively. 3 1.30~1.63g / cm 3 At the same time, by adjusting the process, a relatively complete macroscopic shape can be obtained. This characteristic shows unique advantages for carbon foam when used as a carbon template for porous ceramics and electrodes for supercapacitors. For example, when used as supercapacitor electrodes, the integrity of the electrode can avoid contamination caused by the binder.
[0030] 3. The process design of the present invention is reasonable, the operation is simple, the synthesis equipment is simple, the raw materials are widely available, and the porogen can be recycled. It has good application prospects and can be promoted industrially. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a thermogravimetric curve of the solidified body obtained in step (5) of Example 1 after boiling.
[0032] Figure 2 This is a macroscopic photograph of the foamed carbon in Example 1.
[0033] Figure 3 This is a morphology photograph of the foamed carbon in Example 1.
[0034] Figure 4 This is the XRD pattern of the foamed carbon in Example 1.
[0035] Figure 5 This is the CV curve of the carbon foam in Example 1.
[0036] Figure 6 The EIS spectra of the carbon foam and dense graphite (as a control) in Example 1 when used as counter electrodes of dye-sensitized solar cells. DETAILED DESCRIPTION
[0037] The present invention will be described in detail below in conjunction with the accompanying drawings and specific embodiments. The exemplary embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.
[0038] Example 1
[0039] A method for preparing high-porosity foamed carbon comprises the following steps:
[0040] (1) Mixing: First preheat triethyl phosphate to 100 °C, then add water-soluble starch and mix evenly, and finally add PVDF and stir for 2 h to obtain a mixed suspension;
[0041] The mass ratio of the water-soluble starch to triethyl phosphate is 1:33.05; the mass ratio of the PVDF to the water-soluble starch is 1:0.15; in step (1), the system temperature is always maintained at 100°C.
[0042] (2) Degassing: The mixed suspension was kept at 100°C for 3 hours and then degassed;
[0043] (3) Curing: Pour the degassed mixed suspension into a glass mold preheated to 100°C, and then let it stand at 4°C for 30 min. After the curing, demold the mixture to obtain a cured product.
[0044] (4) Water bath: Soak the solidified body in deionized water at 4°C for 48 hours, replacing the deionized water every 24 hours;
[0045] (5) Boiling: Soak the solidified body after the water bath in deionized water, then heat it to 100°C and boil it for 2 hours. After boiling, take it out and dry it at room temperature.
[0046] (6) Pyrolysis: The solidified body after boiling in water is placed in a tubular atmosphere furnace. First, the temperature is raised to 120°C in an air atmosphere and kept at this temperature for 2 h. Then, the temperature is raised to 700°C in a nitrogen atmosphere and kept at this temperature for 1 h. The heating rate is 5°C / min. Finally, the solidified body is cooled to room temperature to obtain a high-porosity carbon foam.
[0047] The foamed carbon obtained in this embodiment has an apparent porosity of up to 78.63% and an apparent density of 0.35 g / cm 3 , skeleton density is 1.63g / cm 3 .
[0048] Figure 1 : is the thermogravimetric curve of the solidified body after boiling in step (5) of this embodiment. It can be seen from the figure that the residual mass of the solidified body tends to be stable after 700°C, further indicating that PVDF has been completely converted into a thermally stable glassy carbon material.
[0049] Figure 2 This is a macroscopic photograph of the foamed carbon of this embodiment. It can be seen that the prepared foamed carbon has a relatively complete macroscopic shape.
[0050] Figure 3 This is a morphological photograph of the foamed carbon of this embodiment. It can be seen that the foamed carbon contains extremely rich pore structure.
[0051] Figure 4 : is the XRD spectrum of the foamed carbon of this embodiment. The XRD spectrum shows that the foamed carbon is composed of glassy carbon with low crystallinity and can provide a large number of catalytic active sites when used as a catalyst.
[0052] Figure 5 CV curve of the carbon foam in this example. The appearance of two pairs of obvious redox peaks indicates that the carbon foam has better catalytic reduction performance.
[0053] Figure 6 The EIS spectra of the foamed carbon and dense graphite (as a control) used as the counter electrode of the dye-sensitized solar cell in this example are shown in Figure 1. The charge transfer impedance (Rct) of the two is 14.74 and 27.22 Ω cm, respectively. 2 , it can be seen that foamed carbon has better catalytic activity than dense graphite.
[0054] Example 2
[0055] A method for preparing high-porosity foamed carbon comprises the following steps:
[0056] (1) Mixing: First preheat N-methylpyrrolidone to 90 °C, then add water-soluble starch and mix evenly, and finally add PVDF and stir for 2 h to obtain a mixed suspension;
[0057] The mass ratio of the water-soluble starch to N-methylpyrrolidone is 1:30; the mass ratio of N-methylpyrrolidone to water-soluble starch is 1:0.25; in step (1), the system temperature is always maintained at 90°C.
[0058] (2) Degassing: The mixed suspension was kept at 100°C for 2 h, and then degassing was performed;
[0059] (3) Curing: Pour the degassed mixed suspension into a glass mold preheated to 100°C, and then let it stand at 10°C for 40 min. After the curing, demold the mixture to obtain a cured product.
[0060] (4) Water bath: Soak the solidified body in deionized water at 1°C for 72 hours, replacing the deionized water every 24 hours;
[0061] (5) Boiling: Soak the solidified body after the water bath in deionized water, then heat it to 100°C and boil it for 4 hours. After boiling, take it out and dry it at room temperature.
[0062] (6) Pyrolysis: The solidified body after boiling in water is placed in a tubular atmosphere furnace. First, the temperature is raised to 140 °C in an air atmosphere and kept at this temperature for 2 h. Then, the temperature is raised to 900 °C in a nitrogen atmosphere and kept at this temperature for 1 h. The heating rate is 10 °C / min. Finally, the solidified body is cooled to room temperature to obtain a high-porosity carbon foam.
[0063] The foamed carbon obtained in this example has an apparent porosity of 76.15% and an apparent density of 0.33 g / cm 3 , skeleton density is 1.36g / cm 3 .
[0064] Example 3
[0065] A method for preparing high-porosity foamed carbon comprises the following steps:
[0066] (1) Mixing: First preheat triethyl phosphate to 120°C, then add glucose and mix evenly, and finally add PVDF and stir for 3 h to obtain a mixed suspension;
[0067] The mass ratio of glucose to triethyl phosphate is 1:50; the mass ratio of PVDF to glucose is 1:0.30; in step (1), the system temperature is always maintained at 120°C.
[0068] (2) Degassing: The mixed suspension was kept at 120°C for 2 h, and then degassing was performed;
[0069] (3) Curing: Pour the degassed mixed suspension into a glass mold preheated to 120°C, and then let it stand at 1°C for 45 minutes. After the mixture is cured, demold the mixture to obtain a cured product.
[0070] (4) Water bath: Soak the solidified body in deionized water at 10°C for 24 hours, replacing the deionized water every 24 hours;
[0071] (5) Boiling: Soak the solidified body after the water bath in deionized water, then heat it to 100°C and boil it for 2 hours. After boiling, take it out and dry it at room temperature.
[0072] (6) Pyrolysis: The solidified body after boiling in water is placed in a tubular atmosphere furnace. First, the temperature is raised to 135°C in an air atmosphere and kept at this temperature for 2 h. Then, the temperature is raised to 850°C in a nitrogen atmosphere and kept at this temperature for 1.5 h. The heating rate is 10°C / min. Finally, the solidified body is cooled to room temperature to obtain a high-porosity carbon foam.
[0073] The foamed carbon obtained in this example has an apparent porosity of 75.52% and an apparent density of 0.33 g / cm 3 , skeleton density is 1.36g / cm 3 .
[0074] Example 4
[0075] A method for preparing high-porosity foamed carbon comprises the following steps:
[0076] (1) Mixing: First preheat triethyl phosphate to 120°C, then add water-soluble starch and mix evenly, and finally add PVDF and stir for 1 h to obtain a mixed suspension;
[0077] The mass ratio of the water-soluble starch to triethyl phosphate is 1:30; the mass ratio of the PVDF to the water-soluble starch is 1:0.3; in step (1), the system temperature is always maintained at 120°C.
[0078] (2) Degassing: The mixed suspension was kept at 120°C for 4 hours and then degassed;
[0079] (3) Curing: Pour the degassed mixed suspension into a glass mold preheated to 120°C, and then let it stand at 1°C for 15 min. After the mixture is cured, demold it to obtain a cured product.
[0080] (4) Water bath: Soak the solidified body in deionized water at 10°C for 24 hours, replacing the deionized water every 12 hours;
[0081] (5) Boiling: Soak the solidified body after the water bath in deionized water, then heat it to 100°C and boil it for 4 hours. After boiling, take it out and dry it at room temperature.
[0082] (6) Pyrolysis: The solidified body after boiling in water is placed in a tubular atmosphere furnace. First, the temperature is raised to 150°C in an air atmosphere and kept at this temperature for 1 h. Then, the temperature is raised to 1000°C in a nitrogen atmosphere and kept at this temperature for 0.5 h. The heating rate is 20°C / min. Finally, the solidified body is cooled to room temperature to obtain a high-porosity foamed carbon.
[0083] The foamed carbon obtained in this example has an apparent porosity of 81.79% and an apparent density of 0.25 g / cm 3 , skeleton density is 1.36g / cm 3 .
[0084] Example 5
[0085] A method for preparing high-porosity foamed carbon comprises the following steps:
[0086] (1) Mixing: First preheat triethyl phosphate to 80°C, then add water-soluble starch and mix evenly, and finally add PVDF and stir for 3 h to obtain a mixed suspension;
[0087] The mass ratio of the water-soluble starch to triethyl phosphate is 1:50; the mass ratio of the PVDF to the water-soluble starch is 1:0.05; in step (1), the system temperature is always maintained at 80°C.
[0088] (2) Degassing: The mixed suspension was kept at 80°C for 1 hour and then degassed;
[0089] (3) Curing: Pour the degassed mixed suspension into a glass mold preheated to 80°C, and then let it stand at 10°C for 45 minutes. After the curing, demold the mixture to obtain a cured product.
[0090] (4) Water bath: Soak the solidified body in deionized water at 1°C for 72 hours, replacing the deionized water every 24 hours;
[0091] (5) Boiling: Soak the solidified body after the water bath in deionized water, then heat it to 100°C and boil it for 1 hour. After boiling, take it out and dry it at room temperature.
[0092] (6) Pyrolysis: The solidified body after boiling in water is placed in a tubular atmosphere furnace. First, the temperature is raised to 100 °C in an air atmosphere and kept at this temperature for 4 h. Then, the temperature is raised to 500 °C in a nitrogen atmosphere and kept at this temperature for 2 h. The heating rate is 2 °C / min. Finally, the solidified body is cooled to room temperature to obtain a high-porosity carbon foam.
[0093] The foamed carbon obtained in this example has an apparent porosity of 70.87% and an apparent density of 0.43 g / cm 3 , skeleton density is 1.48g / cm 3 .
[0094] Comparative Example 1
[0095] A method for preparing high-porosity foamed carbon comprises the following steps:
[0096] (1) Mixing: Preheat triethyl phosphate to 100 °C, then add PVDF and stir for 2 h to obtain a mixed suspension;
[0097] The mass ratio of PVDF to triethyl phosphate is 1:4.96; in step (1), the system temperature is always maintained at 100°C.
[0098] (2) Degassing: The mixed suspension was kept at 100°C for 3 hours and then degassed;
[0099] (3) Curing: Pour the degassed mixed suspension into a glass mold preheated to 100°C, and then let it stand at 4°C for 30 min. After the curing, demold the mixture to obtain a cured product.
[0100] (4) Water bath: Soak the solidified body in deionized water at 4°C for 48 hours, replacing the deionized water every 24 hours;
[0101] (5) Pyrolysis: The solidified body after the water bath is placed in a tubular atmosphere furnace. First, the temperature is raised to 120°C in an air atmosphere and kept at this temperature for 2 h. Then, the temperature is raised to 700°C in a nitrogen atmosphere and kept at this temperature for 1 h. The heating rate is 5°C / min. Finally, the solidified body is cooled to room temperature to obtain a high-porosity carbon foam.
[0102] The foamed carbon obtained in this example has an apparent porosity of 63.70% and an apparent density of 0.47 g / cm 3 , skeleton density is 1.30g / cm 3 .
Claims
1. A method for preparing high-porosity foamed carbon, comprising the following steps: (1) Mixing: Preheat the organic solvent to 80-120 °C, then add the porogen and mix evenly, and finally add PVDF and stir for 1-3 h to obtain a mixed suspension. (2) Degassing: Keep the mixed suspension at 80-120°C for 2-4 hours, and then degasse; (3) Curing: Pour the degassed mixed suspension into a mold, and then let it stand at 1-10°C for 15-45 minutes. After the curing, demold the mixture to obtain a cured product. (4) Water bath: Soak the solidified body in deionized water at 1-10°C for 24-72 hours; (5) Boiling: Soak the solidified body after the water bath in deionized water, then heat it to 80-120°C and boil it for 1-4 hours. After boiling, take it out and dry it at room temperature. (6) Pyrolysis: The solidified body after boiling is placed in a tubular atmosphere furnace, first heated to 100-150°C and kept warm for 1-4 hours, then heated to 500-1000°C and kept warm for 0.5-2 hours, and finally cooled to room temperature to obtain high-porosity foamed carbon; In step (1), the organic solvent is any one of N-methylpyrrolidone, N,N-dimethylformamide, triethyl phosphate and dimethyl sulfoxide; In step (1), the porogen is water-soluble starch.
2. The method for preparing high-porosity foamed carbon according to claim 1, characterized in that: In step (1), the mass ratio of the porogen to the organic solvent is 1:(30-50); the mass ratio of the PVDF to the porogen is 1:(0.05-0.30).
3. The method for preparing high-porosity foamed carbon according to claim 2, characterized in that: In step (1), the mass ratio of the porogen to the organic solvent is 1:(30-40); the mass ratio of the PVDF to the porogen is 1:(0.10-0.20).
4. The method for preparing high-porosity foamed carbon according to claim 1, characterized in that: In step (1), the system temperature is always maintained at 80-120°C.
5. The method for preparing high-porosity foamed carbon according to claim 1, characterized in that: In step (3), the mold is a glass mold that is preheated to 80-120°C.
6. The method for preparing high-porosity foamed carbon according to claim 1, characterized in that: The step (4) water bath further comprises: during the soaking period, replacing the deionized water every 12 to 24 hours.
7. The method for preparing high-porosity foamed carbon according to claim 1, characterized in that: In step (6), the first heating is carried out in an air atmosphere, and the second heating is carried out in a nitrogen atmosphere; the heating rate of the second heating is 2-20°C / min.
8. A high-porosity foamed carbon prepared by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation method of low-density foamy carbon
CN108455560A
One-step preparation method of light high-strength microsphere phenolic resin-based foamy carbon
CN110921648A
Method for preparing polymer porous nanofiber through mixed phase separation
CN102517673A
Composite stacked and coated lithium ion battery diaphragm and preparation method thereof
CN104393217A
Preparation method of porous carbon material
CN105523539A